Metabolic Response to Stress by the Immature Right Ventricle Exposed to Chronic Pressure Overload. Issue 17 (3rd September 2019) - Kajimoto, Masaki; Nuri, Muhammad; Isern, Nancy G.; Robillard‐Frayne, Isabelle; Des Rosiers, Christine; Portman, Michael A.
Abstract : Background: The right ventricle exposed to chronic pressure overload exhibits hypertrophy and decompensates when exposed to stress. We hypothesize that impaired ability to increase myocardial oxidative flux through pyruvate dehydrogenase leads to hypertrophied right ventricular (RV) dysfunction when exposed to hemodynamic stress, and pyruvate dehydrogenase stimulation can improve RV function. Methods and Results: Infant male Yorkshire piglets (13.5±0.6 kg weight, n=19) were used to assess substrate fractional contribution to the citric acid cycle after sustained pulmonary artery banding (PAB). Carbon 13–labeled glucose, lactate, and leucine, oxidative substrate tracers for the citric acid cycle, were infused into the right coronary artery on 7 to 10 days after PAB. RV systolic pressure, RV free wall thickness, and individual cardiomyocyte cell size after PAB were significantly elevated compared with the sham group. Both fractional glucose and lactate oxidations in the PAB group were >2‐fold higher than in the sham group. Pigs with overdrive atrial pacing (≈80% increase in heart rate) stress after PAB showed only a 22% increase in rate‐pressure product from baseline before atrial pacing and limited carbohydrate oxidation rate in the right ventricle. Intracoronary infusion of dichloroacetate, a pyruvate dehydrogenase agonist, produced higher rate‐pressure product (59% increase) in response to increased workload by atrial pacing in association with a marked increase in lactate oxidation. Conclusions: The immature hypertrophied right ventricle shows limited ability to increase carbohydrate oxidation in response to tachycardia stress leading to energy supply/utilization imbalance and decreased systolic function. Enhanced pyruvate dehydrogenase activation by dichloroacetate increases energy supply and preserves hypertrophied RV contractile function during hemodynamic stress.